MINAT BELI KONSUMEN DILIHAT DARI PERSPEKTIF KELENGKAPAN BARANG DAN TATA RUANG - Nanda Hidayan; Diana Mariya Ulfa (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
This study aims to find out (1) Does the completeness of goods affect consumer buying interest at the Ahsan Amal Supermarkets Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo? (2) Does spatial planning affect consumer buying interest at the Ahsan Amal Supermarket, Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo? (3) Does the completeness of goods and spatial planning have a simultaneous effect on consumer buying interest at the Ahsan Amal Supermarkets in the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo?. The sample used in this study were 80 people of Ahsan Amal supermarket. The method used in this research is multiple linear regression analysis. The data in this study were processed using Microsoft Excel and SPSS 23. The independent variables in this study were the completeness of goods (X1) and spatial planning (X2). The dependent variable in this study is consumer buying interest (Y). The results of this study indicate that the completeness of goods (X1) has a significant effect on consumer buying interest (Y), spatial planning (X2) has a significant effect on consumer buying interest (Y), and the completeness of goods (X1) and spatial planning (X2) significantly simultaneous to consumer buying interest (Y). While the value of the coefficient of determination in this study of 61.4% states that the variation of changes that occur in the consumer buying interest variable of 61.4% can be explained by variations in changes that occur in the variable of completeness of goods and spatial planning, while the remaining 38.6% can expressed by other factors not described in this study